Legality as a principle of court activity in respecting the rights, freedoms and interests of minors in cases of administrative offences - M. A. Sambor (Law and Safety)
The article is devoted to the analysis of the interpretation and peculiarities of implementation of the principle of legality in the court’s activity during the consideration of cases on administrative offences. The study focuses on the empirical aspect of the application by courts of the Constitution and laws of Ukraine regarding the observance of human rights and freedoms in proceedings on administrative offences involving certain categories of citizens who need additional protection – minors. Administrative law enforcement practice demonstrates that the courts of first instance and appellate courts, using their own legal consciousness, apply administrative penalties to minors which are not provided for by law, thereby neglecting the principle of legality in the activities of public authorities. The issue of the right to defence of minors and representation of minors in cases of administrative offences is investigated. It appears that the courts point out that the right to defence of minors is not an obligation of public authorities, but is only a right of a minor. At the same time, it should be noted that the representation of a minor's interests is caused by the fact that he or she does not have full legal capacity and the capacity to act, and therefore is not able to independently use and exercise his or her rights and freedoms.